2017
DOI: 10.1111/hdi.12542
|View full text |Cite
|
Sign up to set email alerts
|

Overview of iron metabolism in health and disease

Abstract: Iron is an essential element for numerous fundamental biologic processes, but excess iron is toxic. Abnormalities in systemic iron balance are common in patients with chronic kidney disease (CKD) and iron administration is a mainstay of anemia management in many patients. This review provides an overview of the essential role of iron in biology, the regulation of systemic and cellular iron homeostasis, how imbalances in iron homeostasis contribute to disease, and the implications for CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
298
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 360 publications
(313 citation statements)
references
References 154 publications
(290 reference statements)
3
298
0
12
Order By: Relevance
“…The results of the current study show there is a negative influence of Fe overload and Fe deficiency on blood vessels. This is in agreement with the report by Dev and Babitt indicating that the influence of Fe overload includes oxidant‐mediated injury, interference with cardiac electrical function, and promotion of vascular fibrosis. Fe deficiency also has adverse consequences on the heart and blood vessels.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the current study show there is a negative influence of Fe overload and Fe deficiency on blood vessels. This is in agreement with the report by Dev and Babitt indicating that the influence of Fe overload includes oxidant‐mediated injury, interference with cardiac electrical function, and promotion of vascular fibrosis. Fe deficiency also has adverse consequences on the heart and blood vessels.…”
Section: Resultssupporting
confidence: 93%
“…Fe deficiency also has adverse consequences on the heart and blood vessels, organs with high energy demands. Some epidemiologic studies in the general population have demonstrated an association between increased heme Fe intake, body Fe stores, and cardiovascular risk . Current European Society of Cardiology guidelines for the diagnosis and management of acute and chronic heart failure recommend assessment of Fe parameters, with ensuing Fe therapy in cases of Fe deficiency…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human beings, it can act as a key component embedded into proteins (e.g., hemoglobin, myoglobin), be a part of enzymes (e.g., myeloperoxidase, nitric oxide synthetases, DNA primase) or play a major role in aerobic electron energy transfer (e.g., respiratory complexes I-III, coenzyme Q10) [8,9]. Our bodies contain about 3-4 g of iron in a heme and non-heme form, though only the minority of it is circulating in the plasma bound to plasma proteins, mainly transferrin [7]. Because of their high reactivity both, ferric (Fe3+) and ferrous (Fe2+) iron are well-protected by chaperones or chelators.…”
Section: Physiology Of Iron In Inflammation and Ros Productionmentioning
confidence: 99%
“…Sin embargo, su exceso genera estrés oxidativo, que es también dañino para la función y supervivencia de las células y tejidos. Por ello es importante mantener la homeostasis del hierro (Figura 2) (14,15) . Uno de los mecanismos que utiliza el organismo para mantener la homeostasis del hierro es evitar su excreción; así, las pérdidas por descamación de células entéricas y otras son del nivel de 1 mg diario, que es lo que habría que reponer con la dieta.…”
Section: Requerimiento De Hierrounclassified